STUDENTS' PERCEPTION OF USING CHARACTER AI TO IMPROVE STUDENTS SPEAKING SKILLS AT PRIMA BANGSA INSTITUTE CIREBON - Veronika Simbolon; Lili Sururi Asipi; Virga Putra Darma (NextGen Education Review Journal, 2025)
The purpose of this study is to explore students' perceptions of the use of Character AI in improving English speaking skills and to identify the limitations or problems encountered by students when practicing speaking with this technology. This study used a qualitative descriptive method conducted in the English Education Study Program at the Prima Bangsa Institute in Cirebon. The participants were eighth-semester students who had used Character AI. Data were collected through observation, interviews, and speaking test. The results of the study show that students have a positive perception of the use of Character AI because it helps improve fluency, pronunciation, and confidence, while also providing more opportunities for practice. However, there are also problems such as technical issues, limited response accuracy, and a lack of natural communication nuances compared to direct interaction. In conclusion, this study confirms that Character AI has great potential as an innovative learning medium for improving speaking skills.